POTENTIAL OF BRAN AS SUBSTITUTION OF GULMA CONTROL IN MANUAL ON RICE PLANTING (Oryza sativa) - Fitria Nugraheni Sukmawati; Dodi Kastono; Rohlan Rogomulyo (Jurnal Agrivet, 2018)
The first aim of this research was to know if brain used on weeds control and changed manual weeds control. The second aim was to know the optimum dosage of bran in any frequency applications on weeds control to increase rice yield. Randomized Complete Block Designe (RCBD) was used and replicated in a three blocks. Analysis of variance was used for data analysis, and than followed with Duncan Multiple Range Test (DMRT) if there was a significant different. Orthogonal Contrast Test was used to know the best treatment in controlled weeds growth. Trend Comparisson Test was used to know the optimum dosage of bran in any frequency applications on weeds control to increase rice yield. The result of this research show that bran could suppress weeds growth and changed manual weeds control, however yet increase rice yield 250 kg/ha of bran wich once and twice application were recommended and treatment combination of 143,33 kg/ha at third application was reach as best combination ti increase rice yield, up to 4,61 ton/ha.Key words: weeds control, manual, bran